Cytokine Levels in Neural Pain in Leprosy - Angst, Débora Bartzen Moraes; Pinheiro, Roberta Olmo; Vieira, Joyce Soares da Silva; Cobas, Roberta Arnoldi; Hacker, Mariana de Andréa Vilas-Boas; Pitta, Izabela Jardim Rodrigues; Giesel, Louise Mara; Sarno, Euzenir Nunes; Jardim, Márcia Rodrigues (Frontiers in Immunology, 2020)
Pain is a frequent symptom in leprosy patients. It may be predominantly nociceptive, as in neuritis, or neuropathic, due to injury or nerve dysfunction. The differential diagnosis of these two forms of pain is a challenge in clinical practice, especially because it is quite common for a patient to suffer from both types of pain. A better understanding of cytokine profile may serve as a tool in assessing patients and also help to comprehend pathophysiology of leprosy pain. Patients with leprosy and neural pain (n = 22), neuropathic pain (n = 18), neuritis (nociceptive pain) (n = 4), or no pain (n = 17), further to those with diabetic neuropathy and neuropathic pain (n = 17) were recruited at Souza Araujo Out-Patient Unit (Fiocruz, Rio de Janeiro, RJ, Brazil). Serum levels of IL1β, IL-6, IL-10, IL-17, TNF, CCL-2/MCP-1, IFN-γ, CXCL-10/IP-10, and TGF-β were evaluated in the different Groups. Impairment in thermal or pain sensitivity was the most frequent clinical finding (95.5%) in leprosy neuropathy patients with and without pain, but less frequent in Diabetic Group (88.2%). Previous reactional episodes have occurred in patients in the leprosy and Pain Group (p = 0.027) more often. Analysis of cytokine levels have demonstrated that the concentrations of IL-1β, TNF, TGF-β, and IL-17 in serum samples of patients having leprosy neuropathy in combination with neuropathic or nociceptive pain were higher when compared to the samples of leprosy neuropathy patients without pain. In addition, these cytokine levels were significantly augmented in leprosy patients with neuropathic pain in relation to those with neuropathic pain due to diabetes. IL-1β levels are an independent variable associated with both types of pain in patients with leprosy neuropathy. IL-6 concentration was increased in both groups with pain. Moreover, CCL-2/MCP-1 and CXCL-10/IP-10 levels were higher in patients with diabetic neuropathy over those with leprosy neuropathy. In brief, IL-1β is an independent variable related to neuropathic and nociceptive pain in patients with leprosy, and could be an important biomarker for patient follow-up. IL-6 was higher in both groups with pain (leprosy and diabetic patients), and could be a therapeutic target in pain control.